Dynamic pathology of islet endocrine cells in type 2 diabetes: β‐Cell growth, death, regeneration and their clinical implications. Issue 2 (15th October 2015) - Yagihashi, Soroku; Inaba, Wataru; Mizukami, Hiroki
Abstract: Diabetes is defined as a disease of hyperglycemic metabolic disorder caused by impaired insulin action or low insulin secretion, resulting in the occurrence of vascular complications. Based on this definition, diabetes therapy has long been oriented to correct hyperglycemia against the specific complications of diabetes. This definition has posed some difficulties, however, in understanding of the pathophysiology of this complicated disease and as such in the establishment of an effective treatment. With continuing efforts to explore the structural basis for diabetes onset and methodological development of immunohistochemistry, progressive decline of β‐cells is now established as a salient feature of type 2 diabetes. Accordingly, diabetes therapy has now turned out to protect β‐cells concurrently with the correction of hyperglycemia. Together with this effort, exploration of the means to regenerate β‐cells or to supply new β‐cells by, for example, induced pluripotential stem cells, are vigorously made with the search for the mechanism of β‐cell decline in diabetes. In the present review, we describe the advances in the islet pathology in type 2 diabetes with special reference to the dynamic alterations of islet endocrine cells in the milieu of maturation, obesity, aging and ethnic differences. The effect of amyloid deposition is also discussed. We hope it will help with understanding the pathophysiology of diabetes, and suggest the future direction of diabetes treatment. Abstract : With the recent progress of pancreas pathology in type 2 diabetes, it becomes clear that islet endocrine cells undergo dynamic alterations of cell growth, death, and regeneration. In addition, transdifferentation from one cell type to another is found to contribute to remodeling of the islet. This review summarizes the alterations of type 2 diabetic islets and points to the possible ethnic differences.